KARAKTERISTIK KECELAKAAN LALU LINTAS AKIBAT PERILAKU MANUSIA PADA RUAS JALAN MAYJEND SUNGKONO KOTA MALANG - Ratnaningsih, Dwi (FSTPT Indonesia, 2015)
The number of motor vehicles increasing impact of the issue of congestion and increasing number of traffic accidents. Roads Maj. Sungkono Kedung Kandang District of Malang has a high accident rate from 2008 to 2012 according to data from Malang Police Unit Laka. Results Analysis of factors affecting the behavior of the traffic accident rate in the Road Mayjend Sungkono Malang include professional actors accidents by 87% is private, the home city of the perpetrators of accidents as much as 53.07% came from Malang,, the age of the perpetrator accident 46.296% is aged 26 -45 years, age pedestrians involved 35.484% age <17th and 17-25th .. Based on the rate of accidents per year in the event of an accident at maximum ie 38.89%.